Kinerja Guru yang Bersertifikasi di SMP Negeri 4 Kecamatan Sirimau Kota Ambon - Eka Kesaulya; Rudolf Kempa; Sumarni Rumfot (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
Teacher performance, the form of behavior referred to by the teacher's activities in the learning process. can be seen when he carries out teaching and learning interactions in class including his preparation both in the form of semester programs and teaching preparation. With regard to the importance of evaluating teacher performance. This study aims to evaluate the performance of certified teachers at SMP Negeri 4 Ambon City. This research was conducted as a qualitative descriptive study with the research subjects being the principal, vice principal, and 5 certified teachers. This study uses a descriptive method with a qualitative approach. As for the subject of this research is the head of the school and teachers. The results of this study are well structured, this is evident. Planning for the performance of certification teachers at SMP Negeri 4 Ambon generally plans according to the provisions, the implementation of certification teacher performance is directed at a good learning process and supervision is carried out with a supervisory system, namely supervisor supervision and functional supervision. Supervision is carried out directly by the school principal and functional supervision is carried out by the school supervisor. Based on the results of the evaluation of the performance evaluation of teacher certification at SMP Negeri 4 Ambon City which was implemented in reality it was going well, but there were also obstacles, namely the learning process had not been carried out and there had to be more improvement for better school progress in the future.